2005
DOI: 10.1016/j.taap.2004.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Guidance values for microcystins in water and cyanobacterial supplement products (blue-green algal supplements): a reasonable or misguided approach?

Abstract: This article reviews current scientific knowledge on the toxicity and carcinogenicity of microcystins and compares this to the guidance values proposed for microcystins in water by the World Health Organization, and for blue-green algal food supplements by the Oregon State Department of Health. The basis of the risk assessment underlying these guidance values is viewed as being critical due to overt deficiencies in the data used for its generation: (i) use of one microcystin congener only (microcystin-LR), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(199 citation statements)
references
References 109 publications
5
192
0
2
Order By: Relevance
“…Calculated possible daily ingestion to avoid acute health problems according to the calculations of Fromme et al (2000). For details, see Dietrich et al (2005) Ingestion route MC concentrations Infants 5 kg = 12.5µg Children 20 kg = 50 µg Adults 60 kg = 150 µg 100 µg kg -1 125 g 500 g 1,500 g Food 10000 µg kg -1 1.25 g 5 g 15 g 100 µg l -1 125 ml 500 ml 1,500 ml Cyanobacterial bloom in lake/river 1000 µg l -1 12.5 ml 50 ml 150 ml 1.0 µg l -1 12,500 ml 50,000 ml 150,000 ml Drinking water 100 µg l -1 125 ml 500 ml 1,500 ml 1.0 µg g -1 12.5 g 50 g 150 g BGAS 10 µg g -1 1.25 g 5 g 15 g …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculated possible daily ingestion to avoid acute health problems according to the calculations of Fromme et al (2000). For details, see Dietrich et al (2005) Ingestion route MC concentrations Infants 5 kg = 12.5µg Children 20 kg = 50 µg Adults 60 kg = 150 µg 100 µg kg -1 125 g 500 g 1,500 g Food 10000 µg kg -1 1.25 g 5 g 15 g 100 µg l -1 125 ml 500 ml 1,500 ml Cyanobacterial bloom in lake/river 1000 µg l -1 12.5 ml 50 ml 150 ml 1.0 µg l -1 12,500 ml 50,000 ml 150,000 ml Drinking water 100 µg l -1 125 ml 500 ml 1,500 ml 1.0 µg g -1 12.5 g 50 g 150 g BGAS 10 µg g -1 1.25 g 5 g 15 g …”
Section: Discussionmentioning
confidence: 99%
“…Based on some major weaknesses in the assumptions underlying the risk assessment leading to this provisional guidance value, Dietrich and Hoeger (2005) concluded that BGAS could pose a serious health risk to consumers, especially children. One of the main weaknesses in the risk calculation process is the assumption that all congeners of a toxin, in this case microcystins have the same toxicokinetic and -dynamic properties, i.e.…”
Section: Specific Health Risks From Contaminated Food and Cyanobactermentioning
confidence: 99%
“…The Guideline for Canadian Drinking Water Quality (Federal-Provincial-Territorial Committee on Drinking Water 2002) sets the maximum acceptable concentration for microcystin-LR at 1.5 μg/L, and the provisional WHO-guideline for drinking water, as well as the Oregon Health Division for blue green algal supplements, currently use microcystin-LR 40 μg/kg/body weight/day as the tolerable daily intake values (Dietrich and Hoeger 2005).…”
Section: Evaluation Of Human Risk Of Microcystin-lr and Nodularinmentioning
confidence: 99%
“…Among cyanotoxins, the hepatotoxin microcystins (MCs) are considered to be one of the most common, toxic, and dangerous cyanotoxins (Chorus and Bartram, 1999). Up to now, more than 80 variants of these intracellular cyclic heptapeptides have been identified (Dietrich and Hoeger, 2005). Presumably, MCs not only promote the development of primary liver cancer (Sekijima et al, 1999), but also initiate liver tumors (Ito et al, 1997).…”
Section: Introductionmentioning
confidence: 99%